Exploring Ways In Which Greenwearfair Can Improve Their Digital Marketing - Muhammad Fathan Kevin Alfputra (Eduvest - Journal of Universal Studies, 2022)
The Covid-19 pandemic, including Indonesia, has an impact on economic instability and one of the affected is Micro, Small and Medium Enterprises (MSMEs) in the fashion sector, which then demands MSME actors in the fashion sector in Indonesia to be creative in marketing their products or services through digital marketing. . This study aims to identify things that need to be improved on Greenwearfair to reach quite a number of customers using digital marketing, determine how to effectively use digital marketing, and describe fashion SMEs in Indonesia using digital marketing to improve marketing. This qualitative research uses a literature study approach. The data collection technique used in this study is documentation in the form of photos that describe digital marketing activities carried out by Greenwearfair and also previous research journals published in 2020-2022 which analyzed the use of digital marketing on MSME actors in Indonesia obtained from Google Scholar and Science. Direct. This study uses a qualitative analysis technique with a deductive approach. The findings of this study indicate that Greenwearfair has marketed its products using digital marketing through social media, namely Instagram and TikTok. However, Greenwearfair must be consistent in posting information about its products, both the consistency of the time and the quality of the postings. We recommend that Greenwearfair make post content more interesting by making video testimonials from influencers so that the target audience is more interested in buying their products.